Diseño de una propuesta para el Mejoramiento Empresarial del Servicio Automotriz, para el Sector de Catambuco en Nariño (2022)
The provision of automotive service today has gained great importance within the global economy, not only in large cities where a large number of of means of transportation, including vehicles or automobiles, that become a means of transportation. sustenance for some and for others as a means of transportation and cargo; This also happens in areas rural areas where they have great potential for economic growth, and with the use of new technologies, their development is moving by leaps and bounds.